2019
DOI: 10.9778/cmajo.20190162
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral arterial disease in Ontario First Nations people with diabetes: a longitudinal population-based cohort study

Abstract: Background: Peripheral arterial disease is an important vascular complication of diabetes that may lead to lower-extremity amputation. We aimed to compare the treatment and complications of peripheral arterial disease between First Nations people and other people in Ontario with diabetes.Methods: Using health care administrative databases, we identified annual cohorts, from 1995/96 to 2014/15, of all people aged 20-105 years in Ontario with a diagnosis of diabetes. We used the Indian Register to identify those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
3
3
0
Order By: Relevance
“…Notwithstanding the difference in the overall LA rates between the two populations (RI and GP), individuals aged 50+ years in both populations had higher rates of LA than those aged 0-49 years. These findings are consistent with those reported in Alberta with LA cases increasing with age, and 47% of LA cases in both RI and GP populations occurred in those aged 65-84 years [35]. Within the age groups, RI were more likely to have LA than GP with RI individuals 0-49 years of age 2.04 times more likely as GP to have LA and RI individuals 50+ years of age 5.33 times more likely as GP to have LA.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Notwithstanding the difference in the overall LA rates between the two populations (RI and GP), individuals aged 50+ years in both populations had higher rates of LA than those aged 0-49 years. These findings are consistent with those reported in Alberta with LA cases increasing with age, and 47% of LA cases in both RI and GP populations occurred in those aged 65-84 years [35]. Within the age groups, RI were more likely to have LA than GP with RI individuals 0-49 years of age 2.04 times more likely as GP to have LA and RI individuals 50+ years of age 5.33 times more likely as GP to have LA.…”
Section: Discussionsupporting
confidence: 91%
“…Our finding that the rate of LA among Saskatchewan RI is 1.7 times higher than GP are supported by observations of LA in RI populations related to diabetes in other Canadian provinces [35][36][37]. Shah et al (2019) examined Ontarians with diabetes and found a 3-5 times higher risk of lower extremity amputation (LEA) in RI than GP populations [35]. Similarly, a study in Alberta found a 3 times higher average age-adjusted rate of LEA in First Nations than Non-First Nations populations with diabetes [36].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Because the OLIS data were acquired at ICES during the present study, we were unable to perform any longitudinal analysis of the links between the levels of glycemic control we observed and the high rates of complications reported in our other papers. [8][9][10][11][12] However, it is highly likely that HbA 1c level sare an important driver of the observed differences in outcomes, given the well-known strong association between glycemic control and complications of diabetes. Leiter and colleagues 47 highlighted the difficulties in achieving glycemic control in their recent report combining results from the Diabetes Mellitus Assessment of Clinical Management in Ontario (DM-ACTION) and Diabetes Mellitus Improving Patient Care in Our Communities (DM-IMPACT) studies.…”
Section: Discussionmentioning
confidence: 99%
“…6 A high incidence of lower extremity amputations among Canada's First Nations populations motivated this study. 4,[7][8][9] We sought to identify health care access barriers among First Nations patients at risk of amputation or who had undergone amputa tion for diabetic foot ulcers in Southern Saskatchewan, explore experiences of patients who had undergone amputa tions for diabetic foot ulcers and those who sought care for diabetic foot ulcers and identify potential solutions to reduce health care barriers.…”
mentioning
confidence: 99%